Analisis Pelaksanaan Penyanderaan Penanggung Pajak Pada KPP Pratama Pematang Siantar Melalui Perkara Gugatan Nomor 29/PDT.G/2021/PN.Pms - Charly Hasibuan; Primandita Fitriandi (Politeknik Keuangan Negara STAN, 2022)
Tax revenues used for national development must continue to be carried out by the government to improve the economy of a prosperous and prosperous society. Therefore, the contribution of tax revenue must continue to be optimized. Optimal tax revenue must be supported by safeguarding state revenues through taxes, namely by collection actions. There is a lawsuit registered at the Pematangsiantar District Court number 29/Pdt.G/2021/PN.Pms filed by the Tax Insurer